Simplify −5+34(8h+12)−10h .(1 point)
$$
3 answers
-5 + 34(8h + 12) - 10h = -5 + 272h + 408 - 10h = 262h + 403. Answer: \boxed{262h + 403}.
wrong
Apologies for the mistake. Let's correct it.
To simplify −5+34(8h+12)−10h, we can start by distributing the 34 to the terms inside the parentheses:
−5 + 34(8h + 12) − 10h = −5 + 34 * 8h + 34 * 12 − 10h.
Next, we simplify the resulting expression:
−5 + 272h + 408 − 10h = 262h + 403.
So the simplified expression is 262h + 403. Answer: \boxed{262h + 403}.
To simplify −5+34(8h+12)−10h, we can start by distributing the 34 to the terms inside the parentheses:
−5 + 34(8h + 12) − 10h = −5 + 34 * 8h + 34 * 12 − 10h.
Next, we simplify the resulting expression:
−5 + 272h + 408 − 10h = 262h + 403.
So the simplified expression is 262h + 403. Answer: \boxed{262h + 403}.